Modeling of Aqueous Root Extract Compounds of Ruellia tuberosa L. for Alpha-Glucosidase Inhibition Through in Silico Study - Safitri, Anna; Sari, Dewi Ratih Tirto; Fatchiyah, Fatchiyah; Roosdiana, Anna (UI Scholars Hub, 2021)
This study aims to analyze the inhibitory activities of aqueous root extract compounds of Ruellia tuberosa L. toward alpha-glucosidase protein by computational docking analysis. Three major compounds contained in the extracts (i.e., betaine, daidzein, and hispidulin) were selected as ligands; quercetin and acarbose were used as the reference. Computational docking analysis was performed using the HEX 8.0.0 program and visualized using the Discovery Studio Visualizer v19.1.0.18287 (2019 version) on the basis of the scoring functions. The interactions between ligands and alpha-glucosidase protein showed different binding patterns. The types of bonds involved in the interaction between the enzyme and these ligands were hydrogen and hydrophobic bonds. Energy generated from docking of betaine, daidzein, hispidulin, quercetin, and acarbose to alpha-glucosidase protein were −167.6, −249.5, −251.2, −241.5, and −322.1 cal/mol, respectively. Acarbose had the lowest energy, indicating that it has the strongest interaction with alpha-glucosidase, followed by hispidulin, daidzein, quercetin, and betaine. Amino acid residues that interacted with the ligands were His717, Met363, Arg608, Pro361, Phe362, Leu865, Glu869, Arg594, andAsp356. The current research shows that R. tuberosa L. aqueous root extracts have the potential to be used as an inhibitor for the alpha-glucosidase protein and as an antidiabetic agent. Nonetheless, further studies are needed to support this modeling study.